As memórias do trauma na reconfiguração da história em K. Relato de uma busca e Os visitantes, de Bernardo Kucinski - Kalinoski, Sandra de Fátima (2020)
This study aims at reflecting, from the perspective of the corpus constituted by the work K. Relato de uma busca (2011) and Os visitantes (2016), by Bernardo Kucinski, about the ongoing necessity of rethinking some recent events of Brazilian history. The first book addresses the family tragedy which devastated the writer’s family during the military governments, referring to the disappearance of his sister Ana Rosa Kucinski and her husband Wilson Silva, victims of the repression regime. The second book revisits some aspects regarding the disappearance questions explored in the first book, however, focusing on discussions and reflections that revisit information, correct it, and update versions of "truth" addressed in the first book. This points to the urgency of a more reflective thinking, attentive to the necessity of continuous updates to the recorded history of these events. In face of the fragmentary writing and testimony that characterize these works, the discussions juxtapose fiction and the preservation of memory silenced by the past. It is a wok of individual memory that is simultaneously representative of a collective issue about the difficulties imposed on this task, immanent to the question of trauma that originates them and characterizes them. Additionally, this work explores the form in which marks left by the contact with the real traumatic events of the Military Dictatorship (1964-1985) are represented in fictional writing. The question of prevented grieving caused by the disappearances during the military regime in Brazil is also discussed. It is perceptible that, in face of the inexistence of funeral rituals due to the negative in returning the corpses to their families, the fiction might serve as an alternative to ritualize grieving, as well as to soften the pain caused by losses. It is knownthat fiction writing allows for the materialization of space of memory dedicated to the victim, space which is inexistent in real life since there are no sepultures for these victims. To achieve these approaches to the aforementioned books, this work is supported on references such as Walter Benjamin, Sigmund Freud, Giorgio Agamben, Paul Ricceur, Jeanne Marie Gagnebin, Márcio Seligmann-Silva, Enrique Serra Padrós, and Eurídice Figueiredo, among others.